THE ROLE OF ISLAMIC EDUCATIONAL PSYCHOLOGY IN CHILD’S SPIRITUAL DEVELOPMENT - Ilham Akbar Maulana; Rini Amelia; Ulfatmi Ulfatmi; Arisa Wahyuni (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2022)
The low spiritual level of the younger generation is signed by the lack of success in Islamic Da’wah referring to them, especially to children. The indicator of the lack of remarked Islamic Da’wah can be seen from five-times prayers at the mosque, which commonly contains the elders or older people; spirituality grows solely when people are getting old or closer to death. This study aimed to examine the role of Islamic educational psychology in developing a child’s spirituality, and the method used was library research. The data was collected by documentation and analyzed by descriptive analysis. The research result showed that psychology is vital to the child’s spiritual development, embedding the awareness of being religiously related to personal spiritual values. In terms of psychology, Islam is known as al-Syakhsiyah. The role of psychological science in developing a child’s spirituality is by bridging the process of delivering spiritual knowledge to be more paid attention to the psychology of every child, starting from the pre-Muhamazis period until he passes the Mumazis period; this will significantly determine the success of transferring values ​​to children.